VD_FINDINFO HC / 2015 / 747 vom 12. August 2015 - VD Tribunal cantonal (2015)
PROTECTION DE L'UNION CONJUGALE, FORTUNE PRIVÉE, ANIMAL DOMESTIQUE | 651a al. 3 CC, 651a CC, 29 al. 2 Cst., 152 al. 1 CPC (CH)